Géopolitique du cyberespace : La cyberstratégie de l’administration Obama - Frédérick Douzet (Bulletin de l’Association de Géographes Français)
The exponential growth of the Internet has generated a proliferation of conflicts between multiple stakeholders —most notably the United States — about its control and regulations, its use in geopolitical conflicts (military and economic warfare, intelligence and soft power), and the respect of civil liberties. This paper shows how the geopolitical approach can help analyze the issues raised and strategies developed by States to reinforce their control and power in cyberspace. The Obama administration’s approach to cyberstrategy has been characterized by an escalation of means and discourses. It should constitute a significant legacy of President Obama in foreign affairs.